Memahami Budaya Tedhak Siten di Masyarakat Jawa: Analisis Pendekatan Moderasi Beragama dan Hukum Islam - Sheptiani Rizki Wulandari; Nur Hidayah; Vrisko Putra Vachruddin (J-Alif : Jurnal Penelitian Hukum Ekonomi Syariah dan Budaya Islam, 2026)
The tedhak siten tradition is one of the Javanese cultural heritages still practiced today by communities to mark the early developmental phase of a child. This tradition not only carries symbolic meaning but also embodies social and religious values related to expressions of gratitude, hope, and the relationship between humans, their environment, and their community. Facing the dynamics of social change and evolving religious understandings, the existence of local traditions such as tedhak siten often sparks debates regarding their compatibility with Islamic teachings. This article aims to analyze the tedhak siten tradition from the perspectives of religious moderation and Islamic law. The study employs a qualitative approach using a literature review method. Data were analyzed using thematic analysis techniques, focusing on the concepts of religious moderation, Islamic law, and cultural ‘Urf. The findings show that the tedhak siten tradition represents a moderate and contextual form of cultural religious practice. From the perspective of Islamic law, this tradition falls within the domain of mu‘āmalah (social transactions) and ‘Urf (customary practice) that is acceptable as long as it does not contradict the basic principles of Sharia. This tradition reflects a harmonization between local culture and Islamic teachings and serves as a means of strengthening religious values and social solidarity within Javanese Muslim society.